Four seasons a Ming emperor and his grand secretaries in sixteenth-century China - Dardess, John W. 1937- (Rowman & Littlefield, 2016)
Richly researched and engagingly written, this important history of imperial China shows in fascinating detail how Emperor Jiajing and his grand secretaries governed. Drawing on a treasure trove of the grand secretaries' personal writings, John W. Dardess's narrative brings to life the inner workings of the largest polity on the face of the earth.